Синтез та властивості продуктів діазоніювання 1(2)-аміно-9,10-антрацендіонів - Лунін, Володимир Вікторович (Національний університет "Львівська політехніка", 2018)
Проведено екзофункціоналізацію 9,10-антрацендіонового кільця 1,2,3-триазолільним фрагментом реакцією 1,3-диполярного циклоприєднання легкодоступних 1(2)-азидів та 1,4(1,5)-діазидів 9,10-антрацендіону з рядом моно- і дизаміщених ацетиленів в умовах купрум (І)-каталізованої реакції. Здійснено арилювання піридину гідросульфатами 9,10-діоксоантраценіл-1(2)-діазонію в умовах модифікованої реакції Гомберга-Бахмана-Хея та досліджено вплив температури в каталітичних та некаталітичних умовах на утворення продуктів реакції. Встановлено, що мажорними продуктами реакції виступають 1-(піридин-2-іл)- та 2-(піридин-2-іл)антрацен-9,10-діони. Запропоновано ефективний підхід до одержання моно- та бісдитіокарбаматів 9,10-антрацендіону в умовах дедіазоніювання діазонієвих солей 1(2)-аміно- та 1,5-діаміно-9,10-антрацендіонів у присутності дитіокарбамінових кислот діетиламіну, морфоліну, піперідіну та піролідіну у водному середовищі без участі каталізатора. Визначено, що дитіокарбамати 9,10-антрацендіону здатні до утворення перхлоратних солей за умов дії 70%-ої HClO4. Встановлено, що реакція дедіазоніювання діазонієвих солей 9,10-антрацендіонів у присутності тритіокарбонатів приводить до утворення виключно сульфідних похідних 9,10-антрацендіону. Запропонована препаративна методика синтезу 9,10-діоксоантраценіл-гідразонів, які містять в іліденовій частині молекули ацильні і/або етоксикарбонільні, карбо- та гетероциклічні фрагменти, та показано їх препаративно зручне використання в одержанні піразольних, тетразольних та амідоксимних похідних. На основі результатів комп’ютерного прогнозування показано напрямки експериментальних досліджень синтезованих сполук. Методами біологічного скринінгу in vitro виявлено сполуки з високою вибірковою антибактеріальною, протигрибковою, антиоксидантною, антитромбоцитарною та протипухлинною дією. The thesis is devoted to the development of ways of synthesis of new diazonation products of 1(2)-amino-9,10-anthracenediones, study of the chemical properties of the diazonation products and study their biological activity. The 1(2)-exofunctionalization of the anthracenedione ring with 1,2,3-triazolyl fragment has been carried out by the reaction of 1,3-dipolar cycloaddition of readily available 1(2)-azido- and 1,4(1,5)-diazido-9,10-anthracenediones with a series of mono- and disubstituted acetylenes under copper(I)-catalyzed conditions. For the first time the arylation of pyridine by diazonium salts of 9,10-anthracenedione have been carried out under the conditions of the modified Homberg-Bachmann-Hey reaction, which leads a mixture of ortho-, meta- and para-isomers of pyridine. It has been determined that the ratio of isomers does not change significantly when temperature condition from -10 °C to +20 °C. A mixture of two pyridine isomers have been obtained at 45-70 °C only in the case of 1-pyridinylanthracenediones. It was determined that the using of copper-catalysis does not significantly influence on this reaction. It’s the evidence of a free-radical mechanism of reaction. The dominant products of arylation of pyridine in the case of 1-pyridinylanthracene-9,10-diones and 2-pyridinylanthracene-9,10-diones have been isolated using preparative chromatography. The experimental and calculated data have shown that ortho-isomers 1-(pyridin-2-yl)anthracene-9,10-dione and 2-(pyridin-2-yl)anthracene-9,10-dione are the major products of the arylation of pyridine. An effective approach for the preparation of mono- and bisdithiocarbamates of 9,10-anthracenedione under the conditions of the dediazonation of the diazonium salts of 1(2)-amino- and 1,5-diamino-9,10-anthracenediones in the presence of dithiocarbamic acids of diethylamine, morpholine, piperidine and pyrrolidine in an aqueous medium without catalyst has been proposed. It was determined that dithiocarbamates of 9,10-anthracenedione have been formed perchlorate salts under the action of 70% HClO4. It has been established that the dediazonization of diazonium salts of 9,10-anthracenedione in the presence of trithiocarbonates leads to the formation of exclusively sulfide derivatives of 9,10-anthracenedione. A preparative method for the synthesis of synthetically important 9,10-anthracenedione-yl-1-hydrazones contained acyl and/or ethoxycarbonyl, carbo- and heterocyclic fragments in the ylidene moiety has been proposed. The convenient preparative variants of synthesis of previously unknown pyrazole and tetrazole derivatives by the interaction of 9,10-dioxoanthracenylhydrazones containing nitrile, acyl and ethoxycarbonyl moieties, with hydrazine hydrate, by refluxing in dioxane or sodium azide by heating in DMF have been developed. The directions of experimental studies of synthesized compounds are shown based on the results of computer prediction. Compounds with high selective bactericidal, fungicidal, antioxidant, antiplatelet and antitumor effects were identified. The promising compound-leader 9,10-dioxo-9,10-dihydroanthracen-1-yl pyrrolidine-1-carbodithioate has been determined, which exhibits antitumor activity against the MCF7 breast cancer cell line, antibacterial action against strains of E. coli, S. aureus, M. luteum, antifungal action against C. tenuis, A. niger and antioxidant activity as the known antioxidant Trolox. It has been established that this dithiocarbamate has moderately toxicity with LD50 >1000 mg/kg. Диссертация посвящена разработке эффективных путей синтеза новых продуктов диазонирования 1(2)-амино-9,10-антрацендионов, изучению их химических свойств и биологической активности. Проведено экзофункционализацию 9,10-антрацендионового кольца 1,2,3-триазольным фрагментом реакцией 1,3-диполярного циклоприсоединения 1(2)-азидов и 1,4(1,5)-диазидов 9,10-антрацендиона с рядом моно- и дизамещенных ацетиленов в условиях медь(I)-катализованной реакции. Осуществлено арилирование пиридина гидросульфатами 9,10-диоксоантраценил-1(2)-диазония в условиях модифицированной реакции Гомберга-Бахмана-Хея и исследовано влияние температуры в каталитических и некаталитических условиях на образование продуктов реакции. Установлено, что мажорными продуктами реакции выступают 1- и 2-(пиридин-2-ил)антрацен-9,10-дионы. Предложен эффективный подход к получению моно- и бисдитиокарбаматов 9,10-антрацендиона в условиях дедиазонирования диазониевых солей 1(2)-амино- и 1,5-диамино-9,10-антрацендионов в присутствии дитиокарбаминовых кислот диэтиламина, морфолина, пиперидина и пирролидина в водной среде без катализатора. Определено, что дитиокарбаматы 9,10-антрацендиона способны к образованию перхлоратных солей в условиях действия 70%-ой HClO4. Установлено, что реакция дедиазонирования диазониевых солей 9,10-антрацендиона с тритиокарбонатами приводит к образованию исключительно сульфидных производных 9,10-антрацендионов. Предложено препаративный путь синтеза 9,10-диоксоантраценилгидразонов, содержащих в илиденовой части молекулы ацильные и/или этоксикарбонильные, карбо- и гетероциклические фрагменты, и показано их применение в получении пирразольных, тетразольных и амидоксимных производных. На основе результатов компьютерного прогнозирования показаны направления экспериментальных исследований синтезированных соединений. Методами биологического скрининга in vitro выявлены соединения с высоким избирательным антибактериальным, противогрибковым, антиоксидантным, антитромбоцитарным и противоопухолевым действием.
Synthesis and properties of diazonation products of 1(2)-amino-9,10-anthracenediones
Синтез и свойства продуктов диазонирования 1(2)-амино-9,10-антрацендионов
Keywords: діазонієві солі аміно-9,10-антрацендіонів; дедіазоніювання; 1,2,3-триазоли; піридиноарилювання; дитіокарбамати; гідразони; піразоли; тетразоли; комп’ютерне прогнозування; біологічна активність; diazonium salts of amino-9,10-anthracenedinones; dediazonation; 1,2,3-triazoles; arylation of pyridine; dithiocarbamates; hydrazones; pyrazoles; tetrazoles; computer prediction; biological activity; диазониевые соли амино-9,10-антрацендионов; дедиазонирование; 1,2,3-триазолы; пиридиноарилирование; дитиокарбаматы; гидразоны; пиразолы; тетразолы; компьютерное прогнозирование; биологическая активность; 547.673.+547.791+547.496.2+547.556.93+547.821.2